2005
DOI: 10.1111/j.1745-7262.2005.00047.x
|View full text |Cite
|
Sign up to set email alerts
|

Combined conventional/antioxidant "Astaxanthin" treatment for male infertility: a double blind, randomized trial

Abstract: Although the present study suggests a positive effect of Astaxanthin on sperm parameters and fertility, the results need to be confirmed in a larger trial before recommending Astaxanthin for the complementary treatment of infertile men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
108
0
10

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(124 citation statements)
references
References 17 publications
3
108
0
10
Order By: Relevance
“…However, only a few of the studies in this review evaluated this outcome, and no definitive answers have yet emerged from these trials. Fifteen in vivo studies 31,36,41,47,50,51,[62][63][64][65][66][67]69,76,82 included pregnancy rate among the end points measured; in two of these studies, a higher pregnancy rate was achieved, but was not statistically significant. 47,76 In another two studies, the pregnancy rate was lower in the antioxidant-treated group than in the control group, although the comparison was against clomiphene citrate or mesterolone rather than placebo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, only a few of the studies in this review evaluated this outcome, and no definitive answers have yet emerged from these trials. Fifteen in vivo studies 31,36,41,47,50,51,[62][63][64][65][66][67]69,76,82 included pregnancy rate among the end points measured; in two of these studies, a higher pregnancy rate was achieved, but was not statistically significant. 47,76 In another two studies, the pregnancy rate was lower in the antioxidant-treated group than in the control group, although the comparison was against clomiphene citrate or mesterolone rather than placebo.…”
Section: Discussionmentioning
confidence: 99%
“…An interesting in vivo study of 60 patients with idiopathic asthenozoospermia who received either placebo or 200 mg day 21 of coenzyme Q10 demonstrated significant improvement in motility after 6 months of treatment; this improvement was markedly reduced after a washout period of 3 months in treated subjects. 81 Comhaire and colleagues 82 reported a study where 30 subfertile men were administered 16 mg day 21 of astaxanthin, a carotenoid that is not converted to vitamin A in humans, for 3 months. No significant improvements in concentration, motility, morphology or volume were seen in the 11 treated men compared with the 19 control patients.…”
Section: Other Compoundsmentioning
confidence: 99%
“…The astaxanthin dose was determined based on safety studies showing that a dose up to 45 mg per day for 4 weeks is well tolerated without serious side effects 19. Long‐term intervention studies (4 mg/day for 52 weeks25; 12 mg/day26 and 16 mg/day for 12 weeks27) reported no serious adverse side effects. The 12 mg daily dose resulted in significant improvement in cognitive measurements 26.…”
Section: Methodsmentioning
confidence: 99%
“…The study also reported that antioxidant intake, to some extent, may attenuate the impact of age on sperm motility. Some studies that implemented an oral antioxidant therapy with different antioxidants were associated with a significant improvement in both spontaneous and assisted conception pregnancy rates [9,11,28,39].…”
Section: Total (95% Ci)mentioning
confidence: 99%